2001
DOI: 10.1385/mo:18:1:51
|View full text |Cite
|
Sign up to set email alerts
|

Serum Levels of IL-1 beta, sIL-2R, IL-6, IL-8, and TNF-alpha in Febrile Children with Cancer and Neutropenia

Abstract: Serum levels of interleukin-1 beta (IL-1beta), soluble interleukin 2 receptors (sIL-2R), interleukin-6 (IL-6), interleukin-8 (IL-8), and tumor necrosis factor-alpha (TNF-alpha) were measured to predict some characteristics of febrile episodes in children with cancer and neutropenia. Forty-eight episodes of febrile neutropenia were determined in 23 pediatric cancer patients, including 35 febrile episodes without identifiable source, 7 episodes of bacteremia due to Gram-negative organisms and 4 due to Gram-posit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
24
2
1

Year Published

2005
2005
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 16 publications
2
24
2
1
Order By: Relevance
“…Our study confirmed the previous results of Persson et al 31 showing that IL-6 and IL-8 can be used for the exclusion of children with bacteremia. In contrast to reports of other authors, [28][29][30] we found that it was not possible to predict bacteremia in children with cancer and fever because of low values of sensitivity and PPV.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Our study confirmed the previous results of Persson et al 31 showing that IL-6 and IL-8 can be used for the exclusion of children with bacteremia. In contrast to reports of other authors, [28][29][30] we found that it was not possible to predict bacteremia in children with cancer and fever because of low values of sensitivity and PPV.…”
Section: Discussioncontrasting
confidence: 99%
“…Stryjewski et al 27 found that IL-8 and procalcitonin (PCT) in combination were good diagnostic markers of bacterial sepsis in children with febrile neutropenia, whereas Soker et al28 showed that sIL-2R, IL-6, and IL-8 may be helpful in the prediction of infection in children with febrile cancer and neutropenia. A prospective, multicenter trial was performed by Santolaya et al29 in which predictors of severe sepsis not clinically apparent during the first 24 hours of hospitalization in children with cancer and febrile neutropenia were evaluated.…”
mentioning
confidence: 99%
“…[18] TNF-α is involved in the regulation of a wide range of biological processes. Similar to our experience, Soker et al, [19] did not find TNF-α to be useful. Abrahamsson et al, [10] reported TNF-α production to be impaired in neutropenic children.…”
Section: Discussionsupporting
confidence: 90%
“…Circulating proinflammatory mediators such as interleukin-6 (IL-6), IL-8, macrophage inflammatory protein-2 (MIP-2), Creactive protein (CRP), and, more recently, procalcitonin (PCT) have been suggested to be predictive for a systemic microbial bloodstream infection in neutropenic hosts (4,8,11,12,24,35,36). However, the early cellular response to gramnegative and gram-positive bacteria is still unclear, and little is known about how the profile of these mediators during severe leukopenia might be affected by different microbial stimuli.…”
mentioning
confidence: 99%